Peran Guru dan Metode Pembelajaran dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Student learning motivation remains an issue in the learning process, influenced by various internal and external factors. External factors, such as less varied teaching methods and the suboptimal role of teachers, often affect students' low motivation. This study aims to understand the role of teachers and teaching methods in enhancing student learning motivation. The method used in this research is descriptive with a qualitative approach, examining the learning process and the factors influencing student learning motivation. The results show that using varied teaching methods and the effective role of teachers as motivators can increase students' learning motivation. Engaging lessons, providing positive feedback, and setting clear learning goals have been proven to motivate students to be more active and enthusiastic in participating in the learning process. The implications of this study emphasize the importance for teachers to develop varied teaching methods and create a supportive learning environment to enhance student motivation, ultimately leading to more optimal student learning outcomes.